EFFECT OF GEOGEBRA TOWARDS STUDENTS' INDEPENDENT LEARNING IN MATHEMATICS - Suci Nuryati Suci; Reflina Reflina (Universitas Muhammadiyah Prof Dr HAMKA, 2023)
Mathematics learning independence can vary among students, with some showing greater initiative than others. This study analyzed the level of independence in learning quadratic functions among junior high school students who were using the GeoGebra application. The study involved 36 Year 9 students and employed a qualitative descriptive method. Data collection techniques included a questionnaire containing 30 positive and negative statements with eight indicators to determine how students respond to independent learning in mathematics using the GeoGebra application. The study found that using the GeoGebra application had a positive impact on learning mathematics, specifically in quadratic functions.